1995
DOI: 10.1002/glia.440130108
|View full text |Cite
|
Sign up to set email alerts
|

Specific attachment and migration of human astrocytoma cells on human but not murine laminin

Abstract: Attachment sites and biological functions of laminin isolated from murine EHS sarcoma have been well studied. Recently several variants of laminin including human placental laminin have been shown to be distinct from EHS-laminin. This study was undertaken to determine attachment, proliferation, and migration phenomena of human astrocytoma cell lines to human and murine sarcoma EHS-laminin. Using short-term attachment assays human placental laminin was shown to be the better substrate for cell adhesion. EHS-lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Laminins, a group of basement membrane glycoproteins consisting of more than 10 different variant forms (Engvall and Wewer, 1996), have been implicated in highly migratory phenotypes of glioma cells (Friedlander et al, 1996;Tysnes et al, 1996). Thus, laminin-1, a prototype laminin variant purified from mouse EHS tumors, was shown to be active in promoting migration of glioma cells prepared from tumor biopsies (Friedlander et al, 1996), while laminin-2 (merosin), another laminin variant prepared from human placenta, was reported to be more active than laminin-1 in promoting adhesion and migration of cultured glioma cell lines (Giese et al, 1995). Roles of other laminin variants in adhesion and migration of glioma cells have not, however, been systematically investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laminins, a group of basement membrane glycoproteins consisting of more than 10 different variant forms (Engvall and Wewer, 1996), have been implicated in highly migratory phenotypes of glioma cells (Friedlander et al, 1996;Tysnes et al, 1996). Thus, laminin-1, a prototype laminin variant purified from mouse EHS tumors, was shown to be active in promoting migration of glioma cells prepared from tumor biopsies (Friedlander et al, 1996), while laminin-2 (merosin), another laminin variant prepared from human placenta, was reported to be more active than laminin-1 in promoting adhesion and migration of cultured glioma cell lines (Giese et al, 1995). Roles of other laminin variants in adhesion and migration of glioma cells have not, however, been systematically investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Tenascin is present in human gliomas, where its increased expression is correlated with angiogenesis (Zagzag et al, 1995). The effects of various matrix proteins on adhesion and migration have also been investigated using cultured glioma cell lines (Friedlander et al, 1996;Giese et al, 1995;Tysnes et al, 1996). Despite these efforts, however, the molecular mechanisms involved in glioma invasion remain poorly understood.…”
mentioning
confidence: 99%
“…That laminin is an inducer of glioma-cell migration has been demonstrated by others (Berens et ul., 1994;Giese et al, 1994Giese et al, , 1995Koochekpour et al, 1995), and this is of considerable interest, since specific ECM glycoproteins may be induced in normal brain tissue in response to invading glioma cells (Pedersen et ul., 1993; J. Knott personal communication). We have recently shown that human glioma cells stably transfected with the lacZ gene also migrate extensively when transplanted into the rat brain (Pedersen et ul., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Laminins, as heterotrimeric glycoproteins comprising a, b and g chains, are biologically active in neoplastic tissues and promote cell motility and growth, angiogenesis and metastasis. [9][10][11][12][13] To date, 5 a, 3 b and 3 g chains have been identified; and combinations of these chains constitute 15 distinct laminin isoforms. 9,12,13 Since cellular responses to the various laminin isoforms are cell-and tissue-specific, laminin expression is dependent on the type of neoplasm.…”
mentioning
confidence: 99%